Combined experimental and theoretical DFT studies on the decorated Pt@Au and Au@Pt electrocatalysts for formic acid oxidation - Yu, Yaolun (2011)
Our aim of this thesis is to make more profound understanding on the origin of the amazing reactivity of the decorated Pt on Au nanoparticle electrocatalyst (decorated Pt@Au) with much lower Pt usage but much higher activity towards formic acid oxidation reaction (FAO) through the combination of experimental approaches and theoretical density functional theory (DFT) calculations. First, the decorated Pt@Au electrocatalyst was synthesized through the Cu under potential deposition (UPD)-Pt redox replacement technique instead of the conventional chemical reduction method. By studying the parameters affecting the Cu UPD process and by carefully calculating the oxidized charge of the UPD Cu through the anode stripping method, we confirmed the successful synthesis of the decorated Pt@Au electrocatalysts within the monolayer range. Compared with the conventional chemical reduction method or electrodeposition method, UPD-redox replacement technique has its unique advantage to synthesize the decorated Pt@Au electrocatalyst with much more precise control of the Pt adlayer throughout the entire process. Pt surface coverage of the as-prepared Pt@Au electrocatalyst could reach extremely low level (≈3%), which could be used as a real model for more fundamental experimental tests and theoretical calculations. Carbon monoxide (CO) strippings have been conducted as a direct link between experiments and DFT calculations on the electrode surface adsorption properties. On the other hand, a series of decorated Au@Pt electrocatalysts was also prepared through the direct electrodeposition method as a parallel experiment and provided us with more detailed information.